Influence Quality Of Service And Facility To Satisfaction Of Patient Take Care Of To Stay With Pain Of Assyifa Paradise Fruit Of Bengkulu South - Aldi Zulfikar; Eska Prima Monique Damarsiwi; Nia Indriasari (Penerbit Jurnal Indonesia, 2022)
Health represent requirement of fundamental to society. More than anything else whole world a period now knocking over by virus of covid-19. Growing of level live society, hence progressively mount also society demand will the quality of kesehatan.Tujuan in this peneilitian that is to know influence of[is quality of Facility and service to satisfaction of patient take care of to stay with Pain of Assyifa Paradise Fruit of Bengkulu South. Method Analysis the used [is] method Test Validity, Test Rehabilitas, classic Test Assumption, Doubled Linear Regression, Kofesien Determensi and Test Hypothesis. Sampel in this research is patient take care of to stay with pain of Assyifa Bengkulu South amounting to 44 people. Result of from research showing Result of Analysis linear regression of bergaanda the is Y = - 1,086+ 0,335 X1 + 0,692 X2. so that this matter depict that variable of x1 and of x2 have an effect on signifikan to variable Y. Coefficient value of determinasi of R square equal to 0,986 . Matter this means that value quality of ( X1) and facility ( X2) have an effect on to satisfaction of patient ( Y) equal to 98,6% while 1,4 % influenced by other variable which we do not is checked in research. Of Neglect test of Crobach that is 0,06 which variable is quality of and facility very reliable to satisfaction of this matter patient is proved with coefficient value is quality of facility and service to officer performance above Neglect of Crobach which have been specified by that is 0,736 and 0,62. Result of classic assumption test [of] value of VIF and of tolerance the quality of facility and service do not influence satisfaction of proved patient with value of VIF and of Tolerence both below/under 10 and above 0,10.